The influence of spatial frequency in partial spatial erasure of holographic diffraction gratings within LiNbO3:Fe - Ince, R.; Yukselici, H.; Ince, A. T.; Tunc, A. V. (ELSEVIER SCI LTD, 2008)
The effect of spatial frequency on partial spatial erasure of a hologram within a photorefractive crystal, lightly doped LiNbO3, was studied by capturing its reconstructed image on a digital camera at times varying from 40s to 420 min after storage. The image's constituent spatial frequencies (6.2-62.3/cm) at these times were studied. Using a capacitor discharge model, lower spatial frequencies (6.2-41.6/cm) discharge exponentially after 180 min, the maximum space-charge field was found to occur for a median spatial frequency of 34.6/cm. Higher spatial frequencies charge continuously. Features oscillating at similar to 2 mu m/s were superimposed on all frequencies >27.7/cm, evolving quadratically to a maximum amplitude at the spatial frequency of 48.5/cm before decaying. It is thought that the refractive-index field stored within the photorefractive crystal caused focussing of the read-out beam leading to the generation of a spatial soliton. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: volume holography; photorefractive effect; partial spatial erasure; digital spatial filter; spatial soliton; INDUCED CHARGE-TRANSPORT; LITHIUM-NIOBATE CRYSTALS; HIGH LIGHT INTENSITIES; IRON-DOPED LINBO3; PHOTOREFRACTIVE CRYSTALS; OPTICAL-PROPERTIES; SOLITONS; LITAO3; DEFECTS; STORAGE; Optics